Are there consistent relationships between major connective tissue components, intramuscular fat content and muscle fibre types in cattle muscle?. (16th June 2020) - Listrat, A.; Gagaoua, M.; Normand, J.; Andueza, D. J.; Gruffat, D.; Mairesse, G.; Chesneau, G.; Mourot, B.-P.; Gobert, C.; Picard, B.
Abstract : Intramuscular connective tissue (IMCT ) is mainly composed of several fibrils (known as total collagen (TCol )) linked between each other by different chemical cross-links (CLs ), the whole being embedded in a matrix of proteoglycans (PGs ). In the field of beef quality, there is limited information on the role of CLs and PGs. Accordingly, several authors suggest that, to investigate the role of IMCT, it is important to investigate them just like TCol and insoluble collagen (ICol ). In muscle, there are two other components, the muscle fibres and intramuscular fat (IMF ) content. There are limited data on the relationships between these three components of muscle and then on possibility to independently manipulate these characteristics in order to control the final quality of meat. The present study aimed to investigate whether consistent relationships exist between these different components of muscle. Therefore, the present study compared four muscles of two cattle types (dairy and beef) to determine associations between TCol, ICol, CLs and PGs. Data were analysed across and within muscle (M ) and animal type (AT ) based on residuals. There was a strong M and AT effect for all muscle characteristics and an interaction M × AT for type I muscle fibres and IMF. Correlations between TCol, ICol and their CLs were M- and AT-independent. Total proteoglycans were positively correlated with TCol and ICol in a muscle-dependent manner irrespective of AT, but no correlation was found with CLs. On the contrary, CLs were negatively correlated with the ratio TPGs : TCol in an M-dependent manner, irrespective of AT. TCol, ICol and CLs were positively and negatively correlated with type IIA and IIB+X muscle fibres only in longissimus thoracis (LT ) muscle, regardless the AT. Insoluble collagen was the only parameter of IMCT to be correlated with type I muscle fibres but only in LT muscle, irrespective of AT. There was no correlation between PGs and muscle fibre types, but PGs were the only IMCT component to be related with IMF in an M-dependent manner, irrespective of AT. Finally, there was no correlation between muscle fibre types and IMF content within M and AT. This study revealed that there is a strong relationship between IMCT components irrespective of M, an M-dependent relationship between the IMCT components and muscle fibre types and few (only with PGs) or no relationship between IMF and IMCT and muscle fibres.